Carrier transport mechanisms of iodine-doped plasma polymerised N, N, 3, 5 tetramethylaniline thin films. (June 2022) - Akther, H.; Rahman, M.Mahbubur; Bhuiyan, A.H.; Kabir, Humayun; Zumahi, SM Amir-Al; Syed, J.A.; Nasrin, Rahima
Abstract: Plasma polymerised N, N, 3, 5 tetramethylaniline (PPTMA) thin films were produced through plasma polymerisation process using aniline derived -N(CH3 )2 as a precursor where N, N, 3, 5 tetramethylaniline (TMA) was used at ambient temperature. As-deposited and iodine incorporated PPTMA layers with smooth and pinholes-free surfaces of several thicknesses ( d ) with structural and electrical (direct current, DC) features were evaluated via various characterisation techniques. The X-ray photoelectron spectroscopic analyses showed that carbon, nitrogen, and oxygen were present on the thin films' surface with different possible groups CO, C-H, C-N, and CC. Both sets of PPTMA films for DC electrical assessment followed Ohmic and non-ohmic conduction in the low ( V Lower ) and high ( V Higher ) voltage areas, respectively. At the V Higher region for both films, space-charge-limited conduction (SCLC) tackle is found to be operative, and the current density ( J ) increases with T and d . The total trap concentration, the free carrier concentration, and the carrier mobility of PPTMA thin films were changed from 4 ± 0.05 × 10 30 m −3, 2 ± 0.04 × 10 21 m −3 and 1.3 ± 0.02 × 10 −13 m 2 V −1 s −1 to 1.2 ± 0.06 × 10 27 m −3, 3.7 ± 0.03 × 10 22 m −3, and 1.5 ± 0.05 × 10 −12 m 2 V −1 s −1 respectively, due to the gradual iodine addition. The activation energy (Δ E ) values of iodine-doped and as-deposited PPTMA films at an applied voltage ( V A = 2 V) from lower ( T L ) to higher ( T H ) temperatures were ~ 0.11 to ~ 0.73 eV (at V A =10 V, 0.10–0.75 eV) and 0.19–0.83 eV (at V A =10 V, 0.18–0.87 eV), respectively. The conductivity of iodine-doped PPTMA films was higher compared to the as-deposited ones. Graphical Abstract: ga1 Highlights: Iodine-doped PPTMA thin films were studied to reveal the carrier conduction mechanism. The presence of C-H, C=C, C-N, and C=O groups were found in the PPTMA structures. Both the Ohmic, and non-Ohmic conductions were detected in the iodine-doped PPTMA thin films. The carrier mobility and free carrier density of the PPTMA thin films were increased with gradual I-doping. The iodine-doping results to enhance the activation energy of PPTMA thin films.